Financial liberalization and access to credit in emerging and developing economies : a firm-level empirical investigation - Gopalan, Sasidaran (2022)
Several emerging market and developing economies (EMDEs) embracing financial liberalization have seen a growing presence of foreign banks in their countries over the last two decades. While foreign banks can contribute to reduced costs of financial intermediation which could result in increased credit availability, there is greater ambiguity about the relationship between foreign bank presence and firms’ access to credit. In this paper, we combine both disaggregate firm-level data from the World Bank Enterprise Survey (WBES) as well as country-data to construct a novel and comprehensive measure capturing firms’ credit constraints as well as information verifiability for firms. Using a firm-level sample of 37,578 observations representing 60 EMDEs covering the time period 2006 to 2014, we employ an ordered probit model on cross-sectional data to understand empirically how foreign banks affect firms’ access to credit. Our results show evidence for foreign bank presence tending to ease firms’ credit constraints. We also find that firms with audited financial statements tend to experience a reduction in credit constraints. Finally, our results point out that for micro, small and medium firms, in relation to the large firms, greater information availability through audited financial statements jointly associated with greater foreign bank presence tends to ease firm credit constraints.